2014
DOI: 10.1002/2013jb010906
|View full text |Cite
|
Sign up to set email alerts
|

Compaction around a rigid, circular inclusion in partially molten rock

Abstract: Conservation laws that describe the behavior of partially molten mantle rock have been established for several decades, but the associated rheology remains poorly understood. Constraints on the rheology may be obtained from recently published experiments involving deformation of partially molten rock around a rigid, spherical inclusion. These experiments give rise to patterns of melt segregation that exhibit the competing effects of pressure shadows and melt‐rich bands. Such patterns provide an opportunity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…In this case, the pressure shadows around the inclusion that are identified by perturbations in the porosity field rotate and advect with the matrix, with the top moving to the right and the bottom to the left, as shown in Figures 2a and 2c (note that all To study the behavior of pressure shadows in more detail, we compute integrals of porosity on the twodimensional slice through the inclusion. Integration is from the local radius of the edge of the inclusion r 5 a to one inclusion radius outward at r52a, for a series of azimuths between 0 and 2p around the circular cross section of the inclusion [Qi et al, 2013;Alisic et al, 2014]:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the pressure shadows around the inclusion that are identified by perturbations in the porosity field rotate and advect with the matrix, with the top moving to the right and the bottom to the left, as shown in Figures 2a and 2c (note that all To study the behavior of pressure shadows in more detail, we compute integrals of porosity on the twodimensional slice through the inclusion. Integration is from the local radius of the edge of the inclusion r 5 a to one inclusion radius outward at r52a, for a series of azimuths between 0 and 2p around the circular cross section of the inclusion [Qi et al, 2013;Alisic et al, 2014]:…”
Section: Resultsmentioning
confidence: 99%
“…This behavior was described in detail by McKenzie and Holness [], Alisic et al . [], and Rudge [] and is discussed further in section B1.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This is expected, as our formulation only addresses the increase of ξ as the porosity φ → 0. However, this sensitivity to ξ/η might not be problematic for realistic applications, as this ratio is expected to be on the order of 1-100 (Hewitt & Fowler 2008;Takei & Holtzman 2009;Simpson et al 2010;Katz 2010;Schmeling et al 2012;Alisic et al 2014).…”
Section: Influence Of Materials Propertiesmentioning
confidence: 99%
“…Thus a detailed study of grain size distributions within the experiments could form a useful test of the theory we have presented here. The natural next step for the development of the theory is to perform a full numerical solution of the governing equations, which will allow a detailed description of the time evolution of the bands (Katz et al 2006;Butler 2012;Alisic et al 2014). With a numerical solution it will be possible to study the connection between the local instantaneous rheology (which we have shown to be effectively strain-rate weakening) and the overall stress-strain curve observed over longer times (which may differ due to the development of the melt bands that concentrate deformation).…”
Section: O N C L U S I O N Smentioning
confidence: 99%